2004
DOI: 10.1128/jcm.42.5.2108-2114.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two 3ABC Enzyme-Linked Immunosorbent Assays for Diagnosis of Multiple-Serotype Foot-and-Mouth Disease in a Cattle Population in an Area of Endemicity

Abstract: The development of a serological test for foot-and-mouth disease virus (FMDV) which is quick and easy to use, which can identify all seven serotypes, and which can differentiate vaccinated from convalescing or potential virus carriers would be a major advance in the epidemiological toolkit for FMDV. The nonstructural polyprotein 3ABC has recently been proposed as such an antigen, and a number of diagnostic tests are being developed. This paper evaluates the performance of two FMDV tests for antibodies to nonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
(41 reference statements)
2
24
0
Order By: Relevance
“…2,3,13,15 The performance of the 4 commercial assays and the single inhouse assay in the current study mirrors those reported in the aforementioned publications, and the implications of this for the application of postoutbreak serosurveillance has been reported separately.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…2,3,13,15 The performance of the 4 commercial assays and the single inhouse assay in the current study mirrors those reported in the aforementioned publications, and the implications of this for the application of postoutbreak serosurveillance has been reported separately.…”
supporting
confidence: 71%
“…However, studies using field sera have suggested a similar relative performance of the 4 commercial NSP tests evaluated here. 2,3 Nevertheless, because of the many factors that will affect the proportion of NSP seropositive animals after an outbreak, as well as the strength of the serologic reactions induced in these animals, it cannot be expected that the diagnostic sensitivity of a test will remain constant nor be fully reflected by the test's performance with a single NSP serum panel. It is intended that the panel be made available to FMD reference laboratories to evaluate new tests and to quality control new batches of existing tests, especially when large diagnostic reserves are being established as part of contingency plans for dealing with future outbreaks.…”
mentioning
confidence: 99%
“…While the diagnostic sensitivity and diagnostic specificity of the 3AB3 indirect ELISA for bovines developed in this laboratory were estimated to 96% and 96.4%, respectively (Mohapatra et al, 2011). The C-ELISAs when compared to the indirect ELISA have near perfect test specificity but compromised sensitivity (Bronsvoort et al, 2004) that also occurred in this study. The whisker plots ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…These results have important implications if the tests are to be used to screen herds or individual cattle in surveillance programs, at border crossings for importexport clearance, or following emergency vaccination in an outbreak situation. 16 In Jordan, Amareen et al 17 reported that the overall seroprevalence of FMD for sheep and goats varied with different NSP tests from 13% to 30% and 73% to 94% in vaccinated and unvaccinated animals, respectively. Similarly, the overall seroprevalence for vaccinated cattle varied with different NSP tests from 30% to 82% with a tests specificity of 92% to 97%.…”
Section: Discussionmentioning
confidence: 99%